High-Speed Sensorless Control for Induction Motor Drives - Dadda Taki Eddine; Guemari Ilyas (University of Shahid Hama Lakhdar - El Oued, 2024)
The project aims to design a sensorless stator field-oriented control algorithm for high-speed drives. However, due to the unavailability of such motors in the university laboratories, a conventional motor with a rated frequency of 50 Hz is utilized. The project is structured into several key subtasks. The introductory chapter provides a comprehensive background, highlighting the advantages, applications, and types of high-speed drives. It offers a comparative analysis of the two primary motor types used in these applications. This chapter also reviews various control methods for high-speed drives and addresses specific challenges and their solutions, thereby delineating the project's scope and limitations. Chapter two is dedicated to the mathematical modeling of the drive system. It begins with the necessary assumptions and proceeds with a formal system description. The mathematical model is constructed and validated using the basic V/f control approach. The detailed design process starts with the fundamental principles of field-oriented control, with a particular emphasis on stator field-oriented control. Subsequent sections delve into the design of the control strategy, including the development of a sensorless control algorithm, flux observer, and speed estimator. The proposed algorithm is rigorously tested and validated through simulation results. Overall, this project systematically addresses the development and validation of a sensorless stator field-oriented control algorithm, providing significant insights into its application for highspeed drives.يهدف المشروع إلى تصميم خوارزمية تحكم موجهة للمجال بدون مستشعر للمحركات ذات السرعات العالية. ومع ذلك، نظرًا لعدم توفر مثل هذه المحركات في مختبرات الجامعة، يتم استخدام محرك تقليدي بتردد مقنن قدره 50 هرتز. يتم هيكلة المشروع إلى عدة مهام رئيسية . يوفر الفصل التمهيدي خلفية شاملة، تسلط الضوء على مزايا وتطبيقات وأنواع المحركات ذات السرعات العالية. يقدم تحليلًً مقارنًا لنوعي المحركات الأساسيين المستخدمين في هذه التطبيقات. كما يستعرض هذا الفصل مختلف طرق التحكم في المحركات ذات السرعات العالية ويعالج التح ديات الخاصة وحلولها، مما يحدد نطاق المشروع وحدود ه. يُخصص الفصل الثاني للنمذجة الرياضية لنظام القيادة. يبدأ بالافتراضات اللًزمة ويستمر بوصف النظام بشكل رسمي. V/f. يتم بناء النموذج الرياضي والتحقق من صحته باستخدام نهج التحكم الأساسي تبدأ عملية التصميم التفصيلية بالمبادئ الأساسية للتحكم الموجه للمجال، مع التركيز بشكل خاص على التحكم الموجه للمجال الساكن. تتناول الأقسام اللًحقة تصميم استراتيجية التحكم، بما في ذلك تطوير خوارزمية التحكم بدون مستشعر، ومراقب التدفق، ومقدر السرعة. يتم اختبار الخوارزمية المقترحة والتحقق من صحتها من خلًل نتائج المحاكا ة. بشكل عام، يعالج هذا المشروع بشكل منهجي تطوير والتحقق من صحة خوارزمية التحكم الموجهة للمجال الساكن بدون مستشعر، مما يوفر رؤى هامة حول تطبيقها في المحركات ذات السرعات العالية
Master's theses: specializing Electrical control
Keywords: Induction motor (IM); Stator Vector control; flux observe; المحرك الحثي ، التحكم الشعاعي للمجال الساكن، مراقب التدفق